THE DOCTRINE OF SUFI PHILOSOPHY AS A POWERFUL ANTIDOTE TO GLOBAL TERRORISM - Saroosh Ahmad Mir (Sekolah Tinggi Agama Islam Sadra, 2024)
The rise of global terrorism presents a critical challenge to peace and stability worldwide, fueled by divisive ideologies that promote hatred and violence. There is a growing need for alternative frameworks that promote understanding, tolerance, and reconciliation. This paper explores the doctrine of Sufi philosophy as a powerful antidote to global terrorism, examining its principles and practices in fostering peace and countering extremist ideologies. A comprehensive review of literature on Sufi philosophy, Islamic mysticism, and counter-terrorism strategies was conducted to elucidate the principles and practices of Sufism in promoting peace and countering extremist narratives. The findings reveal that Sufi philosophy embodies principles of love, compassion, and spiritual enlightenment, potent antidotes to the rhetoric of hatred and violence propagated by extremist groups. Sufi teachings emphasize the interconnectedness of humanity, fostering a culture of tolerance, understanding, and mutual respect. In conclusion, the doctrine of Sufi philosophy offers a transformative framework for countering global terrorism by addressing its root causes of ignorance, fear, and alienation. Through its emphasis on love, compassion, and spiritual enlightenment, Sufism provides a compelling alternative to extremist ideologies, inspiring individuals and communities worldwide to embrace a path of peace, unity, and understanding.